Traditional Chinese Medicine for Alzheimer's Disease and Other Cognitive Impairment: A Review - Pei, Hui; Ma, Lina; Cao, Yu; Wang, Feixue; Li, Zehui; Liu, Nanyang; Liu, Meixia; Wei, Yun; Li, Hao (The American journal of Chinese medicine (1979), 2020)
Cognitive impairment (CI) refers to the dysfunction of memory, language, visual space, execution, calculation, understanding, and judgment in one or more aspects. With global aging, CI will become prevalent worldwide. At present, there is no effective cure for CI. However, Nobel laureate Tu Youyou's research on artemisinin has inspired Chinese researchers to focus on traditional Chinese herbs (TCHs) for the treatment of CI. Traditional Chinese Medicine (TCM) has led to a theory for an independent CI system. The pathogenesis of such impairment involves deficiency, phlegm, and stagnation and involves a range of organs, including the brain, kidneys, heart, liver, and spleen. Our current understanding of the etiology and pathogenesis of this condition has led to the realization that TCHs can improve cognitive dysfunction. Clinical research has shown that TCHs can improve the neuropsychological scale score of patients, the TCM symptom score, and the patient's quality of life. Research has also suggested that TCHs can retard A deposits and tauopathy, regulate the metabolism of cholinergic neurotransmitters, and so on. However, due to their complexity, little is known of the safety and efficacy of TCHs in patients with CI. It is likely that we will be able to identify the precise mechanisms associated with the action of TCHs in such patients due to the integration of multiple technologies. This paper summarizes the pharmacokinetics, curative effect, and mechanisms of action of traditional Chinese herbs in order to provide a scientific basis for the improvement of cognitive dysfunction by TCHs.